LEGAL AND ECONIMIC ASPECTS OF CONTRACTS OF INSURANCE OF CROPS AND YIELDS AGAINST DROUGHT - Veselinović, Janko P; Marković, Todor Đ; Dukić Mijatović, Marijana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
The contract of insurance of crops and yields against drought is based on the risk of decrease of precipitation in comparison with an earlier relevant period. The authors analysed the specificities of the case of draught risk, but also other regulations characteristic of this contractual relationship, both from the economic and the legal point of view. The paper also treats the position of contractual parties in this contractual relationship, partly arising from the monopolising position of the insuring organisation. That part also analyses the contract freedom that is endangered due to unequal positions of contractual parties. Special attention is paid to legal sources, especially the general and special conditions of insurance organisations seeing as they are the main source of law, as there is a lack of legal regulation of this field. The number of Serbian insurance organisations that offer this type of insurance is extremely low, as well as the percentage of insurance against this risk. The authors analyse the reasons for which this type of insurance is underdeveloped in Serbia, as well as the consequences of such a state to a safe agricultural production. The paper also covers the topic of the role of legislators and the state in general, in terms of regulation of certain elements of this contractual relation, but also in terms of state incentives that would contribute to a higher percentage of insured agricultural areas. This would reduce the uncertainty and the damage suffered by agricultural producers due to increasing weather fluctuations. Taking into account the inadequate legal and economic tradition, education in this field would represent a significant contribution to the development of this kind of insurance. The authors analyse the difference between the contracts of insurance of crops and yields against drought and the weather derivative contracts, which can be traded on the stock market.